2008
DOI: 10.1007/s11239-008-0262-6
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin administered to women at 100 mg every other day produces less platelet inhibition than aspirin administered at 81 mg per day: implications for interpreting the women’s health study

Abstract: We found significantly less inhibition of platelet function with the dose used in the WHS than the usual U.S. dose. We observed that the degree of platelet inhibition was significantly less with aspirin 100 mg every other day compared with aspirin 81 mg daily, suggesting that results of the Women's Health Study may have underestimated both the efficacy and toxicity of aspirin as it is commonly administered. These data need to be considered when developing recommendations about the use of aspirin in the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, for efficacy, the dose interval is also a variable. A recent comparison of 81 mg/day aspirin vs. 100 mg every other day to healthy women -mimicking the protocol of the Womens´ Health study, showed that the once daily administration produced stronger and less variable inhibition of platelet function than the 100 mg every second day (65). This suggests that the platelet turnover rate is a variable of aspirin's antiplatelet effect even in healthy volunteers, in particular at (very) low doses An enhanced platelet turnover rate in certain diseases, therefore, might shorten the time of sufficient blockade of platelet COX-1 after aspirin administration and, thereby, reduce its antiplatelet effect and clinical efficacy.…”
Section: Unsolved Issues With Aspirin and Future Aspects Aspirin Vs mentioning
confidence: 99%
“…However, for efficacy, the dose interval is also a variable. A recent comparison of 81 mg/day aspirin vs. 100 mg every other day to healthy women -mimicking the protocol of the Womens´ Health study, showed that the once daily administration produced stronger and less variable inhibition of platelet function than the 100 mg every second day (65). This suggests that the platelet turnover rate is a variable of aspirin's antiplatelet effect even in healthy volunteers, in particular at (very) low doses An enhanced platelet turnover rate in certain diseases, therefore, might shorten the time of sufficient blockade of platelet COX-1 after aspirin administration and, thereby, reduce its antiplatelet effect and clinical efficacy.…”
Section: Unsolved Issues With Aspirin and Future Aspects Aspirin Vs mentioning
confidence: 99%
“…In a direct comparison of aspirin 81 mg daily versus 100 mg every other day in women who otherwise would have met inclusion criteria for The Women's Health Study, daily aspirin was associated with less aspirin resistance than every other day aspirin, suggesting that the results of the Women's Health Study may have underestimated the cardioprotective effects of aspirin. 52 In addition, the Antithrombotic Trialists' Collaboration found in both men and women that doses of aspirin less than 75 mg per day had a nonsignificant decrease in vascular events. 2 Thus, in the Women's Health Study, the total dose of aspirin may simply have been too low, possibly accounting for the observed ineffectiveness in women.…”
Section: Womenmentioning
confidence: 99%
“…However, the variation in doses in the trials was small and is unlikely to be clinically significant. Nevertheless, in healthy women, aspirin 100 mg every other day, the dose used in the WHS, produced less platelet inhibition than 81 mg daily [27], although it is unclear if differences in a platelet function assay are clinically meaningful. It is also noteworthy that a single trial, the WHS, which enrolled exclusively women, contributed approximately 40% of the total subjects, and approximately 78% of the female subjects to the meta-analyses.…”
mentioning
confidence: 99%